Effects of Henna Extract Composite Gelatin Film on the Quality of Beef during Cold Chain Transport and Placement - Feiyu REN; Yajun SHEN; Fang XIANG (Shipin gongye ke-ji, 2022)
In this study, the effects of functional coated films prepared with cuttlefish skin gelatine and henna extract (HAE) as natural preservation agents on the storage loss, colour, colony count, lipid oxidation and the content of haemoglobin, haemoglobin iron and free amino acids in beef mimicking cold chain transportation and retailing for 1, 3, 6 and 8 days were investigated, and the effect of scattered flowers extract composite gelatine films on beef cold storage preservation was comprehensively evaluated. The results showed that the coating treatment effectively prevented water loss and the formation of high iron myoglobin and maintained the water-holding and colour characteristics of the meat samples compared to the uncoated samples (P<0.05). As storage time increased, the HAE+gelatin film significantly extended the shelf life of the meat by reducing the degree of lipid oxidation, the total number of colonies and the number of cold-loving bacteria during storage (P<0.05). Furthermore, depending on the content of free amino acids, the coating treatment significantly reduced the rate of the protein hydrolysis process, while the uncoated samples were hydrolysed faster (P<0.05). Principal component analysis (PCA) showed a high correlation between changes in sample colour and pH, haemoglobin iron content, the occurrence of lipid oxidation and microbial reproduction, which were well inhibited by the HAE+gelatin coating. Therefore, HAE+gelatin coated films can be used as an effective active preservation method for the refrigerated fresh meat.